FRI0350 Investigating the link between ischemic heart disease and behcet's disease: a cross-sectional analysis. (15th June 2017) - Yavne, Y; Tiosano, S; Watad, A; Comaneshter, D; Cohen, AD; Amital, H
Abstract : Background: Behcet's disease (BD) is a multi-systemic chronic inflammatory disorder which involves the vasculature tree of all sizes. Subclinical endothelial injury as a result of chronic inflammation in BD has been associated with thrombosis and arterial stiffness, risk factors for ischemic heart disease (IHD) 1–4 . However, data regarding the association between BD and IHD and the impact of various risk factors on this association, is scarce 3–5 . Objectives: To examine the association between BD and the development of IHD and its potential impact as a cardiovascular risk factor. Methods: This study was conducted as a case-control study utilizing the database of Clalit Health Services. The proportion of IHD was compared between patients diagnosed with BD and age- and gender-matched controls. Univariate analysis was performed using Chi-square and student t-test and a multivariate analysis was performed using a logistic regression model. Results: 871 BD patients and 4, 439 age- and gender-matched controls were included in this study. The proportion of IHD amongst BD patients was increased in comparison with controls (10.9% vs. 7.52% respectively, p -value =0.001). After controlling for cofounders, BD was associated with IHD on multivariate analysis (odds ratio 1.485, 95% confidence interval 1.106–1.982, Table 1 ). When the comparison between BD patients with IHD and controls with IHD was stratified according to risk factors, age younger than 70 and male gender were both found to be significantly elevated in the BD group. Conclusions: BD patients have an increased proportion of IHD in comparison with matched controls. The population of BD patients with IHD has a higher proportion of younger males in comparison with controls with IHD. Preemptive screening for IHD may be warranted in this subgroup. References: Uyar B, Solak A, Genç B, et al. Evaluation of Arterial Stiffness in Patients with Behçet's Disease by Using Noninvasive Radiological Methods such as Intima-Media Thickness of the Carotid, Ankle-Brachial Pressure Index, Coronary Artery Calcium Scoring, and Their Relation to Serum Fetuin-A Levels: A Case-Control Study. Ann Dermatol. 2015;27:702. Springer J, Villa-Forte A. Thrombosis in vasculitis: Curr Opin Rheumatol. 2013;25:19–25. Misra DP, Shenoy SN. Cardiac involvement in primary systemic vasculitis and potential drug therapies to reduce cardiovascular risk. Rheumatol Int. 2016;37.1:151–167. Pandey A, Garg J, Krishnamoorthy P, et al. Predictors of Coronary Artery Disease in Patients with Behcet's Disease. Cardiology. 2014;129:203–206. Seyahi E, Memisoglu E, Hamuryudan V, et al. Coronary atherosclerosis in Behçet's syndrome: a pilot study using electron-beam computed tomography. Rheumatology. 2004;43:1448–50. Disclosure of Interest: None declared